Preferential transmission of minority and drug-resistant clones in polyclonal infections in Mali - Leen N. Vanheer; Emilia Manko; Almahamoudou Mahamar; Jody Phelan; Koualy Sanogo; Youssouf Sinaba; Sidi M. Niambele; Adama Sacko; Sekouba Keita; Ahamadou Youssouf; Makonon Diallo; Harouna M. Soumare; et al. (Malaria Journal)
Abstract Background In polyclonal human malaria infections, the roles of individual clones in human-to-mosquito transmission and their relative transmissibility remain poorly understood. In addition, mutations conferring drug resistance can result in a transmission advantage or disadvantage. Methods Amplicon sequencing of complexity of infection and drug resistance markers was used to analyse post-treatment stage-specific malaria parasite dynamics in human blood infections and in the midguts of mosquitoes that became infected after direct membrane feeding assays (DMFAs). Blood samples originated from 50 asymptomatic Plasmodium falciparum gametocyte-carrying participants. These were collected prior to treatment and at five timepoints over 28 days following a three-day artemisinin-based combination therapy (ACT) regimen of dihydroartemisinin-piperaquine or pyronaridine-artesunate at the Ouélessébougou Clinical Research Unit of the Malaria Research and Training Centre of the University of Bamako (Bamako, Mali). At each study visit, DMFAs were conducted. Results A total of 57 Pfcsp haplotypes and 53 Pftrap haplotypes were identified, indicating high genetic diversity among parasite clones. Prior to treatment, human infections were more often polyclonal and had a higher median multiplicity of infection (MOI; 3 (IQR 2–5)), compared to mosquito midgut infections (1 (IQR 1–2)). At this timepoint, it is likely that some clones detected in human blood are not producing gametocytes and are, therefore, not contributing to mosquito transmission. Minority clones preferentially transmitted, and these same clones often persisted in the human blood samples post-treatment. These observations mirror the rapid decline in asexual parasite density that occurs after ACT initiation, and the more persistent circulation of gametocytes. The data, therefore, suggests that asexual gametocyte-non-producing clones outnumber the gametocyte-producing clones at baseline, yet it is these gametocyte-producing minority clones that are transmitted to and surviving in mosquitoes. Certain haplotypes were also found to be more prevalent in human samples compared to mosquito infections, and vice versa, with 12.6% of haplotypes at baseline exclusively observed in mosquitoes. Along with this, varying odds of transmission for different parasite clones were observed, indicating that there are inherent clonal differences in gametocyte productivity or viability. To assess the transmission of drug-resistant clones, the overall prevalence of molecular markers of drug resistance was determined in both human and mosquito hosts, followed by a pairwise comparison between human blood infections and paired infected midguts. This showed that Asn51Ile in Pfdhfr and Lys540Glu in Pfdhps may have a transmission advantage under ACT, while Ala613Ser in Pfdhps may confer a transmission disadvantage. Conclusions Overall, these findings indicate that parasite dynamics and clonal transmissibility are highly complex, even after ACT. This complexity may have important epidemiological implications, as it suggests the transmission of minority clones and highlights the impact of drug resistance markers on transmissibility.